Analysis of Preventive Psychology in the Story of Prophet Yusuf with His Father, Brothers, and Zulaikha as a Lesson for Preventing Psychological Issues - Fitri, Tiara Yuletha; Waharjani, Waharjani (Indonesian Journal of Multidisciplinary Science, 2026)
The story of the Prophet Yusuf (a.s.) in the Qur'an contains psychological values that are suitable to be studied from the perspective of preventive psychology. This study aims to analyze the dynamics of the relationship between Prophet Yusuf and his father, brothers, and Zulaikha as an illustration of the process of personality formation, emotional management, and self-control in the face of psychological pressure. The method used is a qualitative study with a literature study approach, namely studying the verses of Surah Yusuf. The results of the study show that the Prophet Ya'qub's affection and trust played an important role in building the moral fortitude of the Prophet Yusuf, while the conflict with his brothers reflected the negative impact of unmanaged envy. In addition, the temptation that came from Zulaikha showed the importance of piety and self-control as a form of prevention against deviant behavior. In conclusion, the story of the Prophet Joseph provides a preventive lesson about the importance of fostering moral values, managing emotions, and a healthy environment in maintaining an individual's psychological balance.